"Then They Trust You …": Managing Ergonomics in Home Care. (August 2017) - Love, Marsha; Tendick-Matesanz, Felipe; Thomason, Jane; Carter, Davine; Glassman, Myra; Zanoni, Joseph
The home care workforce, already at 2.7 million caregivers, will become the nation's fastest growing occupation by 2024 as the senior boom generation accelerates the demand for in home services to meet its long-term care needs. The physically challenging work of assisting clients with intimate, essential acts of daily living places home care workers (HCWs) at risk for musculoskeletal disorders (MSDs); yet, HCWs typically receive little formal job training and may lack appropriate assistive devices. In this qualitative pilot study, HCW focus groups described workplace MSD risk factors and identified problem-solving strategies to improve ergonomic conditions. The results revealed that HCWs rely on their behavioral insights, self-styled communications skills and caring demeanor to navigate MSD risks to themselves and increase clients' physical independence of movement. We suggest changes in employer and government policies to acknowledge HCWs as valued team members in long-term care and to enhance their effectiveness as caregivers.